Precision medicine in pediatric solid cancers - Blattner-Johnson, Mirjam; Jones, David T. W.; Pfaff, Elke (Seminars in cancer biology, 2022)
Despite huge advances in the diagnosis and treatment of pediatric cancers over the past several decades, it re-mains one of the leading causes of death during childhood in developed countries. The development of new targeted treatments for these diseases has been hampered by two major factors. First, the extremely heteroge-neous nature of the types of tumors encountered in this age group, and their fundamental differences from common adult carcinomas, has made it hard to truly get a handle on the complexities of the underlying biology driving tumor growth. Second, a reluctance of the pharmaceutical industry to develop products or trials for this population due to the relatively small size of the 'market', and a too-easy mechanism of obtaining waivers for pediatric development of adult oncology drugs based on disease type rather than mechanism of action, led to significant difficulties in getting access to new drugs. Thankfully, the field has now started to change, both scientifically and from a regulatory perspective, in order to address some of these challenges. In this review, we will examine some of the recent insights into molecular features which make pediatric tumors so unique and how these might represent therapeutic targets; highlight ongoing international initiatives for providing comprehen-sive, personalized genomic profiling of childhood tumors in a clinically-relevant timeframe, and look briefly at where the field of pediatric precision oncology may be heading in future.
Gesehen am 11.11.2022